2012
DOI: 10.1155/2012/905823
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV Drug Resistance Mutations in HIV Type 1 Isolates in Antiretroviral Therapy Naïve Population from Northern India

Abstract: Objective. The increased use of antiretroviral therapy (ART) has reduced the morbidity and mortality associated with HIV, adversely leading to the emergence of HIV drug resistance (HIVDR). In this study we aim to evaluate the prevalence of HIVDR mutations in ART-naive HIV-1 infected patients from northern India.Design. Analysis was performed using Viroseq genotyping system based on sequencing of entire protease and two-thirds of the Reverse Transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
(33 reference statements)
3
14
2
Order By: Relevance
“…All the study subjects were found to be infected with HIV subtype C. Other studies also support the dominance of HIV-1 subtype C strains in India [2,10,[16][17][18].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…All the study subjects were found to be infected with HIV subtype C. Other studies also support the dominance of HIV-1 subtype C strains in India [2,10,[16][17][18].…”
Section: Discussionsupporting
confidence: 63%
“…However, the prevalence of primary HIV-DR in the protease gene has been reported to be 14.2% by Arora et al in 2008 [10] [22], and 4% by Deshpande et al in 2011 [23]. Several secondary drug resistanceassociated mutations were also reported by some of these studies [2,10,[19][20][21][22][23]. The M36I mutation in the protease gene (associated with resistance to ritonavir and nelfinavir in B subtype viruses) [15] was found in 35 (67.3%) strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current recommended HIV treatment in India includes two nucleoside reverse transcriptase inhibitors (NRTIs) -zidovudine (AZT) or stavudine (d4T) plus lamivudine (3TC) -in combination with one non-nucleoside reverse transcriptase inhibitor (NNRTI) -nevirapine (NVP) or efavirenz (EFV) -as first-line therapy for ARV-naive patients. Protease inhibitors are used in the second-line treatment regimen [3]. The widespread use of ART is reported to be associated with an impressive decline in the morbidity and mortality of HIV-1-infected patients [4,5].…”
Section: Introductionmentioning
confidence: 99%